Congenital Adhesion Band Presenting as Intestinal Perforation in an Extremely Low Birth Weight Infant - Guillen, Juan; Ramey, Stacey; Parimi, Prabhu Satya (American Journal of Perinatology Reports, 2021)
A 231/7-week-old and 560-g-weighing premature male infant was evaluated on day of life 33 for increased frequency of bradycardias, bilious residual, and an increase in abdominal girth. Physical examination was notable for distended and mild tender abdomen. Investigations revealed pneumoperitoneum with dilated bowel loops and a normal acid–base balance. An urgent exploratory laparotomy demonstrated isolated jejunal perforation with an adhesive band extending from the omentum to the base of the mesentery. A segmental jejunal resection followed by an end-to-end anastomosis was performed. The diagnosis of intestinal perforation was inconsistent with focal spontaneous intestinal perforation and necrotizing enterocolitis. Decision to perform exploratory laparotomy led to diagnosis of congenital adhesion band, a rare clinical condition, and the patient had a favorable outcome. This premature infant made an excellent recovery and the upper gastrointestinal (GI) study demonstrated that the anastomotic site was intact. He is currently tolerating advancing enteral feeds.
Keywords: perforation; congenital band; premature infant; laparotomy